A new reading of the educational dimensions in al-Farabi’s philosophy (Journal of Oriental Studies, 2020)
This paper sheds light on the implications of comprehensive philosophical view of Al-Farabi on education, and the most important features and new progressive educational visions that have not been addressed before in any of the studies. Starting from his comprehensive view of the nature of the universe, existence, man, society, knowledge, mind, and values, Al-Farabi had drawn the features of his philosophical vision of education and the acquisition of science and knowledge, with the aim of community recovery, progress and advancement. Despite strength relationship to power and politicians at their highest levels at that time al-Farabi was not preoccupied with politics, and made his goal to advance man and instill virtue in society. His way to that is to raise the mind, knowledge and morals by which happiness is achieved. Al-Farabi was able to combine the vision of Plato and Aristotle in education and ethics and what the true religion brought, so his educational ideas were realistic and rational, and at the same time they did not violate the principles of Islamic law. Key words: Al-Farabi, philosophical vision, education goals, ethics, methods.